Fracture assessment of V-notched specimens with end holes made of tungsten-copper functionally graded material under mode I loading. (October 2018) - Salavati, H.; Mohammadi, H.; Yusefi, A.; Berto, F.
Highlights: A six layered tungsten-copper functionally graded material is fabricated by powder metallurgy technique. New mode I fracture tests on V-notches with end holes made of W-Cu FGM are summarized. The averaged strain energy density criterion (SED) is employed to investigate the fracture loads of the specimens. The effect of notch geometry on fracture load is elaborated. Abstract: The present research is the first to assess fracture of V-notches with end holes (VO-notches) made of tungsten-copper functionally graded material (W-Cu FGM) under mode I both experimentally and theoretically. W-Cu FGM specimens were fabricated by powder metallurgy technique. A number of fracture tests were carried out on VO-notched W-Cu FGM specimens under mode I for various notch tip radii, notch depths, and notch opening angles. The averaged strain energy density over a well-defined control volume was employed to predict the fracture loads. A numerical approach was used to determine the outer boundary of the control volume. Besides, the effect of notch geometry (notch tip radius, notch depth, and notch opening angle) on fracture load was elaborated. This study demonstrates that SED works well on VO-notched FGM specimens under mode I loading.